NILAI TUKAR PENDAPATAN RUMAH TANGGA PETANI PADI DI DESA TOLOK KECAMATAN TOMPASO KABUPATEN MINAHASA - Vibilia Anggelina Tulong; Charles R. Ngangi; Ellen G. Tangkere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objectiveÂ  of this research to determine the exchange rate of household income of rice farmers in Tolok Village, Tompaso Subistrict. The study was conducted for three months, from May to July 2018. The research site was conducted in Tolok Village, Tompaso District. The method of data collection in this study uses a survey method with the data used in the form of primary data and secondary data. Primary data obtained by direct interviews with respondents based on a list of questions that have been prepared. Secondary data is obtained from relevant agencies. The exchange rate of farmer household income (NTPRP) on farmer expenditure is greater (>) than 1, namely 3.7 farmer's expenditure on food, namely 4.7 and the exchange rate of farmer household income on non-food expenditure, namely 2.1. this means that the average farmer household in Tolok village in Tompaso sub-district can be called prosperous because the income of the farmer's family can not only buy basic necessities but also meet the needs of other farming families.Keywords: Farmer Exchange Rates (NTP), Farmers Income